Formalising Natural Languages with Nooj 2014. - Monti, Johanna (Cambridge Scholars Publishing, 2015)
This volume is composed of 22 peer-reviewed contributions selected from among the 52 presentations submitted for the 2014 International NooJ Conference held at the University of Sassari, Italy.NooJ is a linguistic development environment that allows linguists to formalize a wide range of linguistic phenomena, and then test, adapt, share and accumulate each elementary description so as to build linguistic "modules", that is, structured libraries of linguistic resources. NooJ is also used as a corpus processor that can launch sophisticated queries over large corpora of texts, in order to produce.